Binding Pancreaticojejunostomy: Is It Safe? - Gupta, Sanjay (Niger J Surg, 2020)
BACKGROUND: Postoperative pancreatic fistula (POPF) or leak from pancreaticojejunostomy (PJ) is one of the most common complications after pancreaticoduodenectomy (PD), with an incidence of 5%–30%. Various techniques have been advocated to bring down the incidence of POPF, but there is still none that can be called the “gold standard”. Peng's binding PJ (BPJ) was proposed as a good method of performing PJ with low fistula rates; we present our results with BPJ. METHODS: The data of all patients who underwent PD with BPJ between January 2016 and March 2018 were retrospectively analyzed for demographics, clinical features, type of procedure performed, complications (especially POPF), hospital stay, morbidity, and mortality. RESULTS: A total of 24 patients (18 males and 6 females) were identified. The mean age at the diagnosis was 65.5 ± 6.4 years. Majority of the patients had ampullary carcinoma (62.5%). The most common postoperative complication was delayed gastric emptying seen in 10 patients, whereas only 2 (8.33%) had POPF and there was one mortality. CONCLUSION: BPJ is safe and is associated with a low incidence of POPF.